Interspecific hybridization for transfer of hull-less seed trait from Cucurbita pepo to C. moschata - Barinder Kaur; Karmvir Singh Garcha; Jagdeep Singh Sandhu; Madhu Sharma; Ajmer Singh Dhatt (Scientific Reports, 2023)
Abstract Hull-less seed trait is preferred by nut and oil industries worldwide for snacking and oil extraction as it evades the expensive decorticating (dehulling) process. This seed trait is available in C. pepo only, which has small seed cavity, sensitive to various biotic and abiotic stresses, and restricted to temperate regions for cultivation. Contrarily, the related species C. moschata has wider adaptability, disease tolerance and high seed yield. Therefore, attempt was made to transfer this trait into C. moschata through conventional pollination and ovule culture using four parents of hull-less C. pepo and six of hulled C. moschata. Through conventional approach, few viable F1 seeds (12–23) were obtained by using C. pepo as female parent, but in three crosses (HLP36 × HM1343, HLP36 × HM1022 and HLP44 × HM1022) only, whereas, its use as male parent was not successful. This incompatibility issue of reciprocals was resolved through ovule culture of C. moschata genotypes HM1343 and HM6711 after 17 to 19 days of pollination with C. pepo genotypes HLP53 and HLP72, respectively. The hybridity of interspecific crosses was confirmed through SSR markers (alleles inherited from both the parents), morphological characters and micromorphological leaf traits (differed from both the parents). The successful transfer through interspecific hybridization was further established with the presence of hull-less seed in fruits of F2 populations. Outcome of this study would pave the way for enhancing the productivity and multi-season cultivation of snack-seeded pumpkin even in subtropical and tropical regions.